Baitul Maal wat Tamwil (BMT):Peluang dan Tantangan dalam Pengembangan Lembaga Keuangan Mikro Syariah (LKMS) di Kota Padangsidimpuan - Nofinawati Nofinawati (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
Sharia Micro Financial Institution in a form Baitul Maal Wa Tamwil (BMT)only one unit has operate in Padangsidimpuan. It called BMT Insani Padangsidimpuan. It is located in Pasar Inpres Sadabuan which is establish in 1998. It proved that BMT was not going well in Padangsidimpuan. Even though the majority of the people was Muslim. BMT should have big opportunity to developeSharia Micro Financial Institution in Padangsidimpuan. How ever, BMT in Padangsidimpuan must face many opportunity and challenge to develope Sharia Micro Financial Institution. This paper was conductive to develope BMT as Sharia Micro Financial Institution in Padangsidimpuan and how to the available opportunity and face the challenge to improve BMT as Sharia Micro Financial Institution in Padangsidimpuan.